Poisoning and its Management in Healthcare Facilities in Lagos State, Nigeria - Arinola Joda; Olubusola Olugbake; Oluwaseun Ajetunmobi (Mazandaran University of Medical Sciences, 2020)
Background: Poisons are chemical substances that produce harmful effects on the body. About 0.3 million people die annually from poisoning. Poisons are produced by animals, plants, microorganisms, and food contamination. Poisoning is a global public health problem, especially in children and teenagers and healthcare providers ought to provide protocols for its management. Objectives: The main aim of this study was to document the mode, knowledge of antidotes, and management of poisoning by healthcare providers in selected community pharmacies and hospitals in Lagos state. Methods: This study was a descriptive cross-sectional study. The study data were collected using questionnaires administered to 112 providers in selected community pharmacies and hospitals in Lagos state. The obtained data were collated and analyzed using SPSS version 20.0. Results were presented as frequency tables and charts. Results: A response rate of 85.7% was achieved. The most common mode of poisoning was accidental (89% and 68% among pharmacists and physicians, respectively) and the highest incidence was among children 0-5 years old (41.5% and 48.3% among pharmacists and physicians, respectively). Management was mainly via gastric decontamination with activated charcoal in pharmacies and supportive care in the hospitals. Knowledge and availability of antidotes and management of poisoning were poor. Conclusion: Management of poisoning was generally inadequate and the prominence of a poison control center was recognized. The establishment of poison control centers in healthcare facilities and the organization of updated lectures for healthcare providers will go a long way to improving poisoning management in the state.